Clinical and Anatomical Terminology, Bridging the Gap between Clinical and Anatomical Terminology (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Clinical and Anatomical communication relies on the use of accurate and standard language. Clinical and Anatomical terminologies, while closely related, fulfill distinct roles and address different areas of healthcare. This work examines the history of their development, foundational principles, practical usage, stressing their value in education, clinical practices and research in medicine. It explores challenges associated with standardization and the potential consequences of miscommunications in the medical field.